Development and Evaluation of a Train-the-Trainer Workshop for Hong Kong Community Social Service Agency Staff - Zhou, Qianling; Stewart, Sunita M.; Wan, Alice; Leung, Charles Sai-cheong; Lai, Agnes Y.; Lam, Tai Hing; Chan, Sophia Siu-chee (Frontiers in Public Health, 2017)
Introduction: Capacity building approaches are useful in large-scale community-based health promotion interventions. However, models to guide and evaluate capacity building among social service agency staff in community settings are rare in the literature. This paper describes the development and evaluation of a one-day Train-the-trainer (TTT) workshop for the ‘Enhancing Family Well-Being Project’. The workshop aimed at equipping staff from different community agencies with the knowledge and skills to design, implement and evaluate positive psychology-based interventions in an over-crowded and low-income district in Hong Kong. Methods: The TTT extended and improved on our previous successful model by adding research methods which are important to plan and evaluate the community interventions. Evaluation of the TTT was guided by the Integrated Model of Training Evaluation and Effectiveness (IMTEE), with quantitative and qualitative methods. Quantitative data were collected from pre- (T1), post-training (T2), and six month (T3) and 12 month (T4) follow-up surveys. Qualitative data were collected from four focus groups of agency staff after the intervention. Results: Ninety-three staff from 30 community agencies attended the training, and 90 completed the baseline survey. Eighty-eight, 63 and 57 staff performed the evaluations at T2, T3 and T4 respectively. Agency staff were satisfied with the TTT. Immediate enhancement of knowledge, self-efficacy, and positive attitudes towards the training content was found at T2 (Cohen’s ds: 0.24 to 1.22), all p<0.05). Enhancement of knowledge of all training contents persisted at T3 and T4 (Cohen’s ds: 0.34 to 0.63, all p<0.05). Enhancement of self-efficacy in the use of positive psychology persisted at T3. The skills learned were utilized to conduct subsequent interventions. The staff successfully delivered 23 interventions to 1586 participants; indicated their intention to utilize the skills learned for other interventions and to share these skills with their colleagues. Qualitative feedbacks from 23 staff supported the quantitative results. Conclusion: Our brief TTT was effectively delivered to a large number of agency staff, and showed effects that persisted up to 12 months. Our training and evaluation models may offer a template for capacity building among social service staff for community brief, universal family health interventions in in diverse settings.